2015
DOI: 10.1016/j.clinthera.2015.06.010
|View full text |Cite
|
Sign up to set email alerts
|

“I Do My Best To Listen to Patients”: Qualitative Insights Into DAWN2 (Diabetes Psychosocial Care From the Perspective of Health Care Professionals in the Second Diabetes Attitudes, Wishes and Needs Study)

Abstract: The views of diabetes care professionals are in transition from a conventional hierarchic approach to a PCC approach. Further adoption of this approach would be facilitated by additional psychosocial training and educational/psychological resources, increased teamwork, and societal changes that would make it easier for people to live successfully with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 31 publications
1
32
0
3
Order By: Relevance
“…Evidence suggests that HCPs are beginning to see their role shift from telling patients what to do to listening to patients, although many still feel limited in making this shift by a lack of time and resources (41). In fact, most HCPs recognize and share the values of relationship- and patient-centered care and would love to spend more time with their patients, but cannot afford to do so in a fee-for-service environment that rewards volume over quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that HCPs are beginning to see their role shift from telling patients what to do to listening to patients, although many still feel limited in making this shift by a lack of time and resources (41). In fact, most HCPs recognize and share the values of relationship- and patient-centered care and would love to spend more time with their patients, but cannot afford to do so in a fee-for-service environment that rewards volume over quality.…”
Section: Discussionmentioning
confidence: 99%
“…Providers report that they lack the training to assess barriers to adherence or to know what to do when certain barriers are identified. For example, despite the widespread recognition that psychosocial problems can impair diabetes management, and current American Diabetes Association (ADA) guidelines recommending routine psychosocial screening of all diabetes patients, many providers report insufficient training in assessment and management of psychological difficulties in their patients (41). In addition, many patients lack a consistent provider for diabetes care, creating significant frustration (27) and negatively affecting medication adherence and health outcomes (42,43).…”
Section: Adherence and Health Care Policy And Deliverymentioning
confidence: 99%
“…In practice however, TPE is actually rarely tailored to patients' goals (e.g. Mosnier‐Pudar et al, ; Stuckey et al, ), TPE endpoints are mostly related to treatment adherence or self‐care (Idier et al, ; Fonte et al, ), and psychological issues are not a priority for most HCPs in TPE (Holt et al, ; Bergh et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…First, program tailoring is hindered by the extensively reported lack of time (e.g. Ghorbani et al, ; Stuckey et al, ), and conditions are hardly compatible with HCPs’ empathy (e.g. Brown et al, ; Stuckey et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is often difficult for HCPs to support group-based, person-centered diabetes programs due to a lack of ongoing professional development and supervision [4, 11, 12]. Recent results from the second Diabetes, Attitudes, Wishes and Needs (DAWN2) study revealed that HCPs were inadequately equipped to provide diabetes education, and many had never received postgraduate training [4].…”
Section: Introductionmentioning
confidence: 99%